The Intrinsic Characteristics and Development Trends of Elderly Care Service in China: A Policy Perspective - Jiawen Shi; Pingping Sun; Weinan Liu; Jiangjun Yuan (SAGE Open)
Understanding the policy context of elderly care services, providing scientifically grounded recommendations, and effectively promoting the development of elderly care services in China are of great significance for advancing the nation’s high-level economic and social development. This study employs word frequency analysis to examine elderly care policy documents in China from 2006 to 2022. By focusing on six key dimensions, including the involved stakeholders, and conducting comprehensive, longitudinal, and core analyses of word frequency, the study utilizes summary tables, word clouds, Venn diagrams, and semantic networks to analyze the data. The findings indicate that while the foundation of these policies is relatively stable, the overall development of services remains in the early stages and requires further refinement. Relevant stakeholders in elderly care services should prioritize policy analysis and research, explore the intrinsic characteristics of these policies, understand policy development trends, and formulate better strategies for providing elderly care services. These approaches will contribute to the harmonious and sustainable development of services and ensure improved care for older adults in China.